Relative Contribution of Child Labour to Household Farm and Non-Farm Income in Ghana: Simulation with Child's Education - Isaac Koomson; Simplice A. Asongu (African Governance and Development Institute (AGDI), 2015)
Child labourers play an integral role in households' income diversification process by contributing to farm and non-farm incomes but policies, including that of the ILO have focused largely on eliminating child labour from the agricultural sector through education. This study sought to ascertain the relative contribution of child labourers to farm and non-farm income using the GLSS6 data and employed a SUR estimation that simulated, empirically, with child's education. Findings showed that as a child labourer spends more time in school, every Gh₵1.00 contributed to farm income is accompanied by a Gh₵2.12 contribution towards non-farm income. By implication, child education policy removes child labourers from the farm but are likely to have a paradoxical effect of pushing these children into non-farm activities as they engage in them after school and during weekends. The suggestion is that governments must provide adequate remuneration for workers and pay a good price for agricultural products so that households do not use children as instruments to diversity their income portfolios, since child labour acts as a push factor in the diversification process.
Keywords: I21; J21; J22; J23; Q12; 330; Child labour; Farm income; Non-Farm income; Altruistic; Non-Altruistic